A Neighborhood Shopping Street and the Making of Urban Cultures and Economies in Germany. (June 2014) - Kuppinger, Petra
This paper examines the cultural, social, and economic contributions of multi–ethnic neighborhood businesses to the transformation of German cityscapes. The diversity on N–Street in Stuttgart has been at the forefront of urban transformations and cultural production. I show that neighborhood stores and shopping streets are sites of urban experiments and cultural beginnings which produce new authenticities in the face of rapid urban homogenization. Combining theoretical debates about urban "authenticities, " the creative potential of immigrant neighborhoods, and ethnic/cross–cultural economies, I analyze transformations of N–Street and the surrounding neighborhood. I argue that neighborhood shopping streets are relevant nodes and agents in urban transformations and the production of urban futures. Based on ethnographic fieldwork, I introduce N–Street's history, its current configuration of genuinely local urban cultures and economies, and its cultural complexity and cultural and economic innovation. Una Calle Comercial de un Barrio y la Producción de Culturas y Economías Urbanas en Alemania Este artículo examina las contribuciones culturales, sociales y económicas de negocios en barrios multi–culturales para la transformación del paisaje urbano de Alemania. La diversidad en Calle–N en Stuttgart ha estado a la cabeza de las transformaciones urbanas y producción cultural. Muestro que las tiendas de barrio y las calles comerciales son lugares de experimentación urbana y de iniciativas culturales que producen nuevas autenticidades con miras a una rápida homogeneización urbana. Combinando debates teóricos sobre "autenticidades" urbanas, analizo las transformaciones de Calle–N y del barrio alrededor. Sugiero que las calles comerciales de barrio son nodos y agentes relevantes en las transformaciones urbanas y en la producción de futuros urbanos. En base a trabajo de campo etnográfico presento la historia de Calle–N, su actual configuración de genuina cultura y economía local, y su complejidad cultural e innovación cultural y económica.